Effects of thinning intensity on nutrient concentration and enzyme activity in Larix kaempferi forest soils. Issue 1 (December 2016) - Kim, Seongjun; Han, Seung; Li, Guanlin; Yoon, Tae; Lee, Sang-Tae; Kim, Choonsig; Son, Yowhan
Abstract Background As the decomposition of lignocellulosic compounds is a rate-limiting stage in the nutrient mineralization from organic matters, elucidation of the changes in soil enzyme activity can provide insight into the nutrient dynamics and ecosystem functioning. The current study aimed to assess the effect of thinning intensities on soil conditions. Un-thinned control, 20 % thinning, and 30 % thinning treatments were applied to aLarix kaempferi forest, and total carbon and nitrogen, total carbon to total nitrogen ratio, extractable nutrients (inorganic nitrogen, phosphorus, calcium, magnesium, potassium), and enzyme activities (acid phosphatase, β-glucosidase, β-xylosidase, β-glucosaminidase) were investigated. Results Total carbon and nitrogen concentrations were significantly increased in the 30 % thinning treatment, whereas both the 20 and 30 % thinning treatments did not change total carbon to total nitrogen ratio. Inorganic nitrogen and extractable calcium and magnesium concentrations were significantly increased in the 20 % thinning treatment; however, no significant changes were found for extractable phosphorus and potassium concentrations either in the 20 or the 30 % thinning treatment. However, the applied thinning intensities had no significant influences on acid phosphatase, β-glucosidase, β-xylosidase, and β-glucosaminidase activities. Conclusions These results indicated that thinning can elevate soil organic matter quantity and nutrient availability, and different thinning intensities may affect extractable soil nutrients inconsistently. The results also demonstrated that such inconsistent patterns in extractable nutrient concentrations after thinning might not be fully explained by the shifts in the enzyme-mediated nutrient mineralization.